2012
DOI: 10.1210/en.2012-1329
|View full text |Cite
|
Sign up to set email alerts
|

Nursing During the First Two Days of Life Is Essential for the Expression of Proteins Important for Growth and Remodeling of the Neonatal Porcine Cervix

Abstract: The neonatal porcine cervix is sensitive to hormones, including relaxin (RLX), from birth. Whether nursing is required to establish the cervical developmental program or to determine cervical developmental trajectory is unknown. The objective of study 1 was to determine effects of age and nursing on expression of molecular markers and mediators of porcine cervical growth and remodeling from birth to postnatal day (PND) 2 and to document effects of RLX treatment during this period on expression of targeted gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 41 publications
3
20
0
Order By: Relevance
“…Here, results show that imposition of the lactocrine-null state for 2 days from birth, by substituting milk replacer feeding for nursing, changed the uterine developmental program by PND 2 such that the developmental trajectory of the endometrium was altered at histomorphological, cellular, and molecular levels on PND 14. These studies support and extend findings for the cervix [41] by showing that returning colostrum-deprived gilts to nursing after PND 2 fails to rescue uterine endometrial phenotype. Results provide evidence that lactocrine signaling during the first 48 h of neonatal life triggers cell compartmentspecific gene expression events and affects related cell behaviors that drive endometrial morphogenesis.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Here, results show that imposition of the lactocrine-null state for 2 days from birth, by substituting milk replacer feeding for nursing, changed the uterine developmental program by PND 2 such that the developmental trajectory of the endometrium was altered at histomorphological, cellular, and molecular levels on PND 14. These studies support and extend findings for the cervix [41] by showing that returning colostrum-deprived gilts to nursing after PND 2 fails to rescue uterine endometrial phenotype. Results provide evidence that lactocrine signaling during the first 48 h of neonatal life triggers cell compartmentspecific gene expression events and affects related cell behaviors that drive endometrial morphogenesis.…”
Section: Discussionsupporting
confidence: 83%
“…Earlier studies indicated that nursing is required for establishment of neonatal porcine uterine [40] and cervical [41] developmental programs between birth and PND 2. Present results confirm and extend those findings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations